Naturalness Is in the Eye of the Beholder - Clement, Charles R.; Levis, Carolina; Cabral de Oliveira, Joana; Fausto, Carlos; Mendes dos Santos, Gilton; Fontes Baniwa, Francineia; Mehinaku, Mutuá; Wajãpi, Aikyry; Wajãpi, Rosenã; Sodré Maia, Gabriel (Frontiers in Forests and Global Change, 2021)
World conservation discourse concentrates on forests of high naturalness, which are variously termed intact forest landscapes, primary forests, pristine forests, and wilderness. In this essay, we bring Amazonian indigenous perspectives to this discussion, both because they have the right to be in the discussion and because they have a lot to teach us about naturalness. It is essential to understand that indigenous ontologies do not distinguish culture from nature, since all beings, humans and non-humans, are part of a network of social-ecological interactions. Hence, forests are not natural, but the domus of different beings who inhabit, care for and cultivate them. Each part of the forest mosaic in different stages of social-ecological succession has different owners: when people open swiddens, they must respect other forest residents to do so, and when they fallow their swiddens, other forest residents reassume their original roles as managers and conservers of that part of the mosaic. Each stage of the succession also contains cultivated and domesticated plant populations, so we can think of a different kind of conservation: that of genetic resources. From this perspective, swidden-fallow represents on farm conservation, while less anthropogenic parts of the forest mosaic represent in situ conservation. We believe that reframing forest conservation and learning from indigenous people can inspire innovative conservation science and policies.